Varieties of Indonesian Negation in Indonesian Children’s Speech - Bernadette, Kushartanti; Nazarudin, Nazarudin; R. Niken, Pramanik (Pusat Pengajian Ilmu Kemanusiaan, 2019)
Negation is an important concept that has to be learned by children, even in the first years of their life. There are several categories of meaning in negation. In child language studies, there are three main semantic categories of negation. The order of the types indicates the stage of language acquisition: a) REJECTION/REFUSAL; b) DISAPPEARANCE / NONEXISTENCE /UNFULFILLED EXPECTATION; c) DENIAL (Pea, 1980). In Indonesian, there are four standard negative particles: tidak that negates actions and states; belum expressing undone or unifinished certain activities or states; bukan negating objects or things; and jangan for imperatives. There are also nonstandard Indonesian negative particles, used generally in informal situations, namely nggak that has the equivalent meaning to tidak and belom/blom that equals to belum. To produce negative constructions, Indonesian speakers only have to put certain negative markers preceding certain words, for example jangan ‘do not’ + bergerak ‘move’, or tidak ‘not’ + sakit ‘sick’. This is why the production of negation is acquired earlier by Indonesian-speaking children, compared with their Indo-European-speaking counterparts. When they reach the age of two, children already use the four Indonesian negative particles: nggak ‘no, not’, belum ‘not yet’, jangan ‘don’t’, and bukan ‘not’ (see Dardjowidjojo, 2000; Raja, 2006).